Participation in the Ngozi goat crossbreeding project (Burundi) and associated changes in the farming systems - Rey, B.; Jacob, U. (International Goat Association, 1993)
A survey was conducted on 224 randomly selected farmers, comprising those participating and non-participating in a goat corssbreeding project in Burundi, and 54 farmers chosen as `breeders' by the project. Participating farmers were similar to the average goat farmers in the region in terms of land size (0.86 ha) and quality, and labour force available on the farm (labour force unit). The flock size was unchanged (6 heads), but its composition showed an increase in the proportion of Alpine crossbreds in participating farmers' flocks with a decline in the proportion of Small East African goats. Involvement in the crossbreeding programme was associated with differences in the cropping system (more fodder crops, maize and patatoes). With the adoption of the promoted practices, the livestock system required more labour and appeared to substitute off-farm employment for the head of household, indirectly indicating the profitability of farming dual=purpose goats. The project effectively adressed representative farmers, but was modifying the farming system far beyond the goat component. In contrast recently selected `breeders' had larger flocks and land holding than average participating farmers.